Enhancing Grid Stability and Power Quality in Renewable Energy Integration using STATCOM - Mustafayeva, Gulshan (ADA University, 2023)
Wind and solar energy gain popularity among renewable sources due to their cost-effectiveness, widespread availability, scalability. Nonetheless, integration of Green Energy Sources can lead to a reduction of power quality at the point of common coupling (PCC), introducing harmonic components into electrical networks. It is crucial for these harmonics to stay within predefined limits to avoid potential adverse effects [24]. The acceptable level for power quality has dependency from the sensitivity of the installed load [25]. Various factors, including network strength, load characteristics, utilization of electronic equipment, geographical location, network length, climate conditions, operational practices of utility operators, affect the frequency and occurrence of power quality issues. Principal components of Renewable Energy Sources (RES) - Power Electronics (PE) converters in Photovoltaic (PV) and wind generation systems introduce high-level harmonics that have the potential to harm connected devices, diminishing their efficiency and lifetime. Additionally, these converters heavily depend on the quality of the voltage signal. Therefore, it is crucial to enhance power quality by implementing diverse measures to establish the smooth operation of the system [2]. Power quality problems arise when there are abnormalities in voltage or current waves, and their regularity is influenced by the strength of the system, presenting challenges particularly in the context of renewable sources. To enhance the power quality of Renewable Energy Sources (RESs), various measures are implemented, including the implementation of improved control strategies and the use of different auxiliary devices. These measures encompass sub-categorizations such as filters, flexible AC transmission systems (FACTS) devices, energy storages, and converter control, all aimed at improving power quality. Addressing power quality issues in PV/wind systems involves the application of advanced filtering technologies like active and passive filters [33]. However, the drawback of Passive Filters (PFs) lies in their cost, size, and weight dependence on the power rating of converters. Such devices as inductors and capacitors behave as reactive power receivers or delivers provide fixed level of compensation, consequently, PFs may not be the optimal solution [34,33]. On the contrary, a highly attractive solution is the utilization of flexible AC transmission systems (FACTS) to enhance various aspects of power quality, including harmonics, power factor, oscillations in electrical quantities, and voltage dips, especially in systems with high renewable penetration. An example of a FACTS device, the Static Synchronous Compensator (STATCOM), is introduced in the paper to address power quality problems in renewable energy systems.
Keywords: Renewable energy sources – Power quality – Harmonics; Power quality – Wind power – Solar power; Flexible AC transmission systems (FACTS) – Power quality; Wind power – Power electronics – Harmonics control; IT and Engineering